(untitled) (Contemporary Journal of Social Science Review, 2025)
The Holy Qur’an holds a unique position as the divinely revealed scripture that has remained untouched by human alteration. The preservation of the Qur’an is an unparalleled phenomenon in human history, achieved through divine promise and human efforts. This paper explores the various methods employed for the protection and memorization of the Qur’an. The discussion delves into traditional and contemporary techniques, emphasizing their foundational significance. Key strategies include oral transmission, the role of huffāz (memorizers), and advancements in digital technology for preservation. Furthermore, the paper underscores the cultural, spiritual, and educational value of Qur’anic memorization. By examining historical and current practices, the study aims to highlight the collective efforts and divine facilitation that ensure the Qur’an’s integrity and accessibility for all generations.